Reação de variedades de Phaseolus vulgaris L. a seis raças fisiológicas da ferrugem identificadas em Minas Gerais - Junqueira Netto, Arnoldo; L Athow, Kirk; Vieira, Clibas (Revista Ceres, 2025)
The reaction of 30 varieties of bean (Phaseolus vulgaris L.) to six physiologic races of rust (Uromyces phaseoli var. phaseoll) FM-8, FM-10, FM-16, FM-19, FM-21, and FM-26. Identified in the state of Minas Gerais, were studied.